Immediate-implant-based-breast-reconstruction with two-stage expander-implant reconstruction versus one-stage-reconstruction with acellular dermal matrix: analysis of patients’ satisfaction - Innocenti, Alessandro; Melita, Dario; Affortunati, Marco; Susini, Tommaso; Innocenti, Marco (Acta Biomedica Atenei Parmensis, 2021)
BackgroundThe aim of this retrospective study is to evaluate the patient-reported outcome after immediate ADM-assisted implant- based breast reconstruction.Material and MethodsPatients underwent breast reconstruction from 2015 to 2019 have been retrospectively divided into group A (partial subpectoral implant and ADM and group B (expander/implant). For each patient we evaluated retrospectively postoperative complications and patients’ satisfaction.Results26 patients from the case group and 40 from the control group completed the BREAST-Q. The incidence of complications in the cases was 18.4%, while in the control group was 20.4%.  We found no statistical difference in most of the domains and in the mean score of the questionnaire (mean score cases=69.0±14.4 vs controls=68.4±15.7; p=0.888). A significant difference results only in the domains Q2a and Q2b, sensation of rippling.Conclusions. The use of ADM in one-stage reconstruction allows to perform breast reconstruction in only one surgery, with similar complication rates and patient satisfaction.